Determinants of technological innovations in health tourism enterprises - Elżbieta Szymańska; Eugenia Panfiluk (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The research problem is the implementation of technological innovations in health tourism services. The main purpose of the paper is diagnosing determinants of technological innovativeness of enterprises that provide health tourism services. Two detailed objectives were laid down-specifically, an indication of these determinants in respect of the range and type of a technological innovation. The methods applied in the research are: Delphi method, comparative analysis, the range method and the standardised interview method. In order to indicate determinants the following research techniques were used: Kruskal-Wallis test, factor analysis, analysis of medium-rank test, Spearman's rank order correlation test. The primary result is diagnosing determinants affecting technological innovativeness of the subjects under study which are: quality of endogenous human capital of the surveyed entities and inflow of external information. The research is of ground-breaking nature since until now, technological innovations in health tourism have not been described in economy literature. The results have an impact on the development of economics and management sciences, contributing to the development of innovation theory and enterprise management. Moreover, the results potentially contribute to the practical aspect by means of their application by practitioners-organisers of health tourism.
Keywords: I15; L83; O30; 650; some innovations; radical innovations; technology; tourism; health tourism